What is 5x + y = 10
Solve the equation and find the y value for the given x value
x = -2

Answers

Answer 1
Answer: 5(-2) + y = 10
-10 + y = 10
plus 10 on both side to get rid of 10 in left side
10 - 10 + y = 10 + 10
y = 20
Answer 2
Answer:

Answer:

y=20

Step-by-step explanation:

5x+y=10 can't be solved without one of the values but with given the value of x, we can substitute the equation...

-----> 5(-2)+y=10

5 times -2 is -10

-----> -10+y=10

Now we add 10 to each side that leaves y on its own and adds 10 with another 10 making 20 on the other side.

------> y=20

I hope this helps! :)


Related Questions

How many acute/obtuse/right angles does a pentagon have
would you describe the situation with a negative number. The Titanic rests at a depth of about 12,000 feet
What is (-7x + 1) + (-x + 2)
Solve the equation 2/5x - 1 = 9. Complete the solution and check your solution.
Simplify (2x^{2} - 5x + 3) - (-x^{2} + 4x - 5)

-2p-4=2 please Help me

Answers


                                 -2p - 4 = 2

Add  4  to each side:        -2p = 6

Divide each side by  2 :      -p = 3

Multiply each side by  -1 :    p = -3


To get the answer we have to obtain single p on the LHS.
-2p-4=2      /:-2   (divide both sides by -2)
p+2=-1      /-2    (subtract 2 both sides)
p=-3 - its the answer

Determine and prove what shape is formed for the given coordinates for ABCD, and then find theperimeter and area as an exact value.
A (10,-4), B (6,-7), C (3,-3), D (7,0)

Answers

Answer:

Square

Step-by-step explanation:

Plot points A (10,-4), B (6,-7), C (3,-3), D (7,0) on the coordinate plane.

Find slopes of the sides:

AB:\ (-7-(-4))/(6-10)=(3)/(4)\n \nBC:\ (-3-(-7))/(3-6)=-(4)/(3)\n \nCD:\ (0-(-3))/(7-3)=(3)/(4)\n \nDA:\ (-4-0)/(10-7)=-(4)/(3)

The slopes of opposite sides are the same, so opposite sides are parallel. The slopes of adjacent sides have product of -1, then adjacent sides are perpendicular.

Find the lengths of all sides:

AB=√((10-6)^2+(-4-(-7))^2)=√(4^2+3^2)=√(16+9)=√(25)=5\ units\n \nBC=√((6-3)^2+(-7-(-3))^2)=√(3^2+4^2)=√(16+9)=√(25)=5\ units\n \nCD=√((3-7)^2+(-3-0)^2)=√(4^2+3^2)=√(16+9)=√(25)=5\ units\n \nAD=√((10-7)^2+(-4-0)^2)=√(3^2+4^2)=√(16+9)=√(25)=5\ units\n \n

All four sides are of the same length.

Quadrilateral ABCD is a square (all sides of equal length and perpendicular)

Consider solving the equation for x.3(3x + 4) - 5 = ax + b
Which statements are true about the solution to the equation when substituting values for a and b as specified?
Select all that apply.

A. If a=−3 and b=4 , then there is exactly one solution to the equation.
B. If a=−9 and b=13 , then there is no solution to the equation.
C. If a=9 and b=−2 , then there is no solution to the equation.
D. If a=−3 and b=−5 , then there are infinitely many solutions to the equation.
E. If a=9 and b=7 , then there is exactly one solution to the equation.

Answers

Answer:

A. If a=−3 and b=4 , then there is exactly one solution to the equation.

C. If a=9 and b=−2 , then there is no solution to the equation.

Step-by-step explanation:

The given equation is

3(3x+4)-5=ax+b

To solve for x, we need to use the distributive property

3(3x+4)-5=ax+b\n9x+12-5=ax+b\n9x-ax=b-7\nx(9-a)=b-7

To find the right statement, we need to the given values.

For a=-3 and b=4,

x(9-a)=b-7\nx(9-(-3))=4-7\nx(9+3)=-3\n12x=-3\nx=(-3)/(12) =-(1)/(4)

So, choice A is true, because there's one solution to the equation.

For a=-9 and b=13,

x(9-a)=b-7\nx(9-(-9))=13-7\n18x=6\nx=(6)/(18)=(1)/(3)

The choice B is false.

For a=9 and b=-2

x(9-a)=b-7\nx(9-9)=-2-7\n0x=-9\n0=-9

Choice C is correct, because there's no solution, because zero is not equal to -9.

For a=-3 and b=-5

x(9-a)=b-7\nx(9-(-3))=-5-7\n12x=-12\nx=(-12)/(12)=-1

Choice D is false, becuase there's only one solution.

For a=9 and b=7

x(9-a)=b-7\nx(9-9)=7-7\n0x=0\n0=0

Choice E is false, because there are infinite solutions in ths case.

Therefore, the right choices are A and C.

So let's simplify the equation first.

9x + 12 - 5 = ax + b
9x + 7 = ax + b
9x - ax - b = 7

Alright now plug in the numbers for each option.
I don't feel like doing all of them but I did A (one solution) and B (no solution because the two 9x's cancel out).

Which equation represents the line that passes through points (0, 6) and (2, 0)?y=-3x+2
y=-3x+6
y=-3x+2
y=-3x+6

Answers

Answer:

y=-3x+6

Step-by-step explanation:

Equation of line passing through two points:

Equation\ of\ line\ passing\ through\ two\ points\ (x_1,y_1)\ and\ (x_2,y_2)\n\n(y-y_1)=((y_2-y_1))/((x_2-x_1))(x-x_1)\n\n(x_1,y_1)=(0,6)\n\n(x_2,y_2)=(2,0)\n\n(y-6)=((0-6))/((2-0))(x-0)\n\ny-6=(-6)/(2)(x-0)\n\ny-6=-3(x-0)\n\ny-6=-3x\n\ny=-3x+6

15 students wore pj's out of 20 . how many were not wearing pj's in decimal

Answers

15/20 = 3/4 were wearing pajamas

3/4=0.75, so only 0.25 were not wearing pajamas.
15
----=3\4=0.75 
 20

75
-50
-----
25

Lisa has a 12% discount coupon for a clothing store. She sees a new purse that she wants to buy. After the 12% discount was applied, Lisa paid $52.80 for the purse. What was the original price of the purse?

Answers

12% discount, paid $52.80

She paid 12% less than the full price, so:
100%-12%=88%

88% of the original price = $52.80
1% of the original price = $52.80 ÷ 88 = 0.6

Therefore,
100% of the original price = 0.6 x 100 = $60.00

THE ANSWER:
The original price of the purse was $60.00